Dampak Pandemi Covid-19 Terhadap Nilai Harga Saham Syariah di Indonesia - Hasya Mazaya Lathifah; Dewi Santi Febrianti; Anisa Putri Utami; Atiqah Athi Ulhaq; Tulasmi Tulasmi; Titania Mukti (ITB AAS INDONESIA Surakarta, 2021)
COVID-19 Pandemic has brought several direct impacts in Indonesia to make every sector decrease especially in Capital Market since March 2020. COVID-19 is the main impact that affected to decrease the value of ICI in every sector on the stock exchange. However, there is a sector that seems capable to survive during the Pandemic, which is the consumer goods industry sector. One of the successful sectors coming from the consumer goods industry sector is the pharmacy business sector (INAF and KAEF). The research aims to analyze INAF and KAEF stocks during the Pandemic, whether both stocks can survive or not by using a various approach such as global economy, the impact of foreign and domestic policies, the effect of PSBB (Large-scale Social Restrictions), also the lockdown which being held in March-December. The method that is used is qualitative, as the data were collected from ISE (Indonesia Stock Exchange) and Yahoo Finance. The result of this research shows that INAF and KAEF stocks can survive and highly increase the stock price during the COVID-19 Pandemic.